Comparison of visual observation and emission intensity of resazurin for antimicrobial properties of hexane, dichloromethane, methanol and water extracts from a brown alga, Turbinaria ornata. Issue 1 (31st December 2016) - Tye, Kar-Yee; Gan, Sook-Yee; Lim, Swee-Hua Erin; Tan, Sou-Eei; Chen, Chen-Ai; Phang, Siew-Moi
Abstract: Marine natural products have been increasingly found to be a promising source of drug candidates for fighting human diseases. The present study was carried out to assess the antimicrobial properties of a brown alga, Turbinaria ornata . Hexane, dichloromethane, methanol, and water extracts were tested against 23 micro-organisms including Gram-positive and negative bacteria, yeasts, and fungi. The disk diffusion method was employed followed by modified resazurin microtitre assay (REMA). The results obtained from modified REMA using both methods of colorimetric and fluorometric were compared. The best antimicrobial activity was recorded in dichloromethane extract for disk diffusion. Further, modified REMA showed inhibition in Bacillus cereus, Bacillus subtilis, Staphylococcus aureus ATCC 25923, S. aureus, Staphylococcus epidermidis, Staphylococcus saprophyticus, Enterococcus faecalis, Pseudomonas aeruginosa ATCC 27853, Candida parapsilosis ATCC 22019, Candida guilliermondii ATCC 6260, and Saccharomyces cerevisiae . Both methods of modified REMA were substantially in agreement with each other based on Cohen's kappa statistical analysis ( κ value = 0.712; p < 0.0005). Our findings suggested that T. ornata dichloromethane extract has the potential to be used as a source of antimicrobial compounds.